2022
DOI: 10.3390/life12020166
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Membranes Contribute to Drug Transport across the Feto-Maternal Interface Utilizing the Breast Cancer Resistance Protein (BCRP)

Abstract: During pregnancy, the placenta is established as a primary organ for drug transport at the maternal-fetal interface. The fetal membranes (FM) also form an interface with maternal tissues; however, their role in drug transport has not been previously investigated. Knowledge of drug transport across this feto-maternal interface along with the placenta can improve new drug development and testing for use during pregnancy. We also hypothesize that extracellular vesicles (exosomes 30–160 nm) released from the FM an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Our recent findings have shown the functionally active transporter proteins including phosphoglycoprotein-1, breast cancer receptor protein-1, and organic anion transporter proteins in fetal membranes. 12,13 Current study has shown the protein and gene expression of several active influx and efflux transporters proteins and active cytochrome 3A4 enzyme capable of metabolizing drug molecules, in human fetal membrane cell lines (data in press). Therefore, simultaneous testing of both FMis will be necessary to fully understand the effect of a drug's potential impact during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent findings have shown the functionally active transporter proteins including phosphoglycoprotein-1, breast cancer receptor protein-1, and organic anion transporter proteins in fetal membranes. 12,13 Current study has shown the protein and gene expression of several active influx and efflux transporters proteins and active cytochrome 3A4 enzyme capable of metabolizing drug molecules, in human fetal membrane cell lines (data in press). Therefore, simultaneous testing of both FMis will be necessary to fully understand the effect of a drug's potential impact during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent findings have shown the functionally active transporter proteins including phospho-glycoprotein-1, breast cancer receptor protein-1, and organic anion transporter proteins in fetal membranes. 12,13…”
Section: Introductionmentioning
confidence: 99%
“…[13,19] A few of these transporter proteins include permeability-glycoprotein (P-gp), breast cancer resistance protein-1 (BCRP-1), and the organic anion transporting polypeptide 2B1 (OATP2B1) were primarily localized in the chorion with limited expression in the amnion. [12,13] Their expression and function in the fetal membranes are similar to that observed in the placenta, changing the dogma that the placenta is the only intrauterine organ responsible for molecule transport. [12] Further studies and a better understanding of this drug transportation route may lead to novel therapeutic approaches and innovative drug therapies during pregnancy.…”
mentioning
confidence: 84%
“…[12,13] Their expression and function in the fetal membranes are similar to that observed in the placenta, changing the dogma that the placenta is the only intrauterine organ responsible for molecule transport. [12] Further studies and a better understanding of this drug transportation route may lead to novel therapeutic approaches and innovative drug therapies during pregnancy. This is critical, as a breakdown of the homeostatic processes of the fetal membranes described above leads to catastrophic membrane failure.…”
mentioning
confidence: 84%
“…If this phenomenon occurs at the maternal–fetal interface is still unclear, but we cannot exclude the possibility that some phytocannabinoids could have a higher local relevance than previously suspected and that Cannabis may affect placental permeability towards other phytochemicals and toxicants, especially in case of polysubstance abuse by pregnant women. Being that the BCRP/ABCG2 efflux transporter is highly expressed on the apical surface of syncytiotrophoblasts, where it modulates the trafficking of toxicants from maternal circulation to the developing fetus during prenatal growth [ 145 ], its downregulation could expose the fetus to detrimental effects of the xenobiotics, including Cannabis constituents.…”
Section: The Ecs: a Modulatory System For A Successful Pregnancymentioning
confidence: 99%